Inelastic displacement spectra for Chinese highway bridges characterized by single-degree-of-freedom bilinear systems. Issue 14 (October 2019) - Wu, Yi-feng; Li, Ai-qun; Wang, Hao
As for the inelastic displacement demand of a single-degree-of-freedom system, previous studies usually focus on the strength reduction factor, R, or the inelastic displacement ratio, C . Only a little literature reports the direct statistical results of the mean inelastic displacement spectra, S d . Based on 308 earthquake records selected from three types of site soil, differences between the direct mean S d and the indirect ones that respectively derived from mean R and mean Cμ are investigated, in which Cμ refers to the constant ductility inelastic displacement ratio. It is found the indirect S d will introduce errors for using mean R and mean Cμ, while the dispersion of the direct spectra need to be reduced before putting into practice. Two methods, the period normalized method and the spectra-matching method, are employed to address the dispersion problem, and the latter one that modified a record to make its acceleration response spectra compatible with the specified standard, Chinese highway bridge seismic design guidelines in this study, works with more acceptable performance. Finally, a comprehensive equation is proposed to characterize the spectra-matching mean S d, the practicality and efficiency of the identified parameters in the equation are verified. It is advisable to use the proposed equation to assess the inelastic displacement demand of Chinese highway bridges characterized by single-degree-of-freedom bilinear system, and the procedures to obtain the displacement spectra can also be utilized for other corresponding researches.